Factors Influencing the Progression and Direction of Scoliosis in Children with Neurological Disorders - Yeun-Jie Yoo; Jung-Geun Park; Leechan Jo; Youngdeok Hwang; Mi-Jeong Yoon; Joon-Sung Kim; Seonghoon Lim; Bo-Young Hong (MDPI AG, 2022)
(1) Background: scoliosis is highly prevalent in children with neurological disorders, however, studies predicting the progression and affecting the direction of scoliosis have been insufficient. We investigated the factors associated with the progression and direction of scoliosis in children with neurological disorders. (2) Method: retrospectively, 518 whole spine radiographs from 116 patients were used for analysis. Factors affecting the progression of scoliosis over time were analyzed using linear mixed-effects model. Factors associated with the apex direction of the scoliosis were analyzed. (3) Results: pelvic obliquity (PO) ≥ 2.5°, gross motor function classification system level V, vertebral rotation, and female sex significantly affect the progression of scoliosis (p = 0.04, <0.001, <0.001, 0.005, respectively). The higher side of PO and the apex side of scoliosis were interrelated (χ² = 14.58, p < 0.001), but the asymmetrical neurological upper extremity involvement was not. (4) Conclusions: severely impaired gross motor function, PO, vertebral rotation, and female sex were significantly related to the progression of scoliosis. The higher side of PO was opposite to the apex side of scoliosis. By identifying the factors that influence the progression of scoliosis, patients at high risk could be more actively intervened to minimize the severe complications.